Intensified nitrogen removal in the tidal flow constructed wetland-microbial fuel cell: Insight into evaluation of denitrifying genes. (10th August 2020) - Wang, Longmian; Zhou, Ying; Peng, Fuquan; Zhang, Aiguo; Pang, Qingqing; Lian, Jianjun; Zhang, Yimin; Yang, Fei; Zhu, Yueming; Ding, Chengcheng; Ni, Lixiao; Cui, Yibin
Abstract: A novel tidal flow constructed wetland coupled with a microbial fuel cell system (TFCW-MFC), using the influent chemical oxygen demand (COD)/total nitrogen (TN) ratio of 10:1 (Device A) and 5:1 (Device B), systematically assessed nitrogen attenuation and power production performance; the spatiotemporal distribution characteristics of denitrifying functional genes and their relationship with nitrogen removal were also determined. The results showed that the TFCW-MFC achieved high removal efficiencies for COD and TN, with both devices above 95% and 83%, respectively. The maximum power density showed a notable increase from 16.97 in Device B to 25.78 mW/m 3 in Device A. The distribution of the Shannon index indicated that the diversity of nap A, nir K, and nir S were higher at the cathode layers in two devices. The high COD/TN ratio obviously increased the nir K diversity in anode on the 30th day, while a low COD/TN ratio apparently promoted the diversities increase of nar G, nir K, and nir S in upper or bottom layers. Proteobacteria was the dominant phylum in both devices, and the composition differentiation of the dominant denitrifying genera was mainly affected by the space variation, specifically the nitrogen concentration, pH, dissolved oxygen, and their collaborative roles, rather than the COD/TN ratio. Furthermore, TN removal was very significantly positively correlated with voltage and the relative abundance of Rhodanobacter . In summary, this study provided an insight for the key functional genes shaping the enhanced nitrogen removal by the newly designed TFCW-MFC system. Graphical abstract: Image 1 Highlights: TN removal rates in two TFCW-MFC devices with different C/N ratios were above 83%. The highest diversities of nap A, nir K, and nir S were present at the cathode. The dominant denitrifying functional genes belonged within Proteobacteria. C/N had a more effect on denitrifier diversity than its community composition. TN removal was significantly positively correlated with Rhodanobacter and voltage.